Nominal group technique application towards design of components and elements of non-digital game framework - Siti Khadijah Anis; Alias Masek; Muhammad Nurtanto; Nur Kholifah (Institute of Advanced Engineering and Science, 2022)
Non-digital games are a tool that can help children to build and improve problem solving skills in early mathematics learning. Teachers need to design a learning activity using non-digital games taken account problem solving skills in the learning activities. However, the application of problem-solving skills in early mathematics learning activities is challenging, as there is no specific reference that can be used as a guide in implementing effective learning activities. The nominal group technique (NGT) approach is used to design the main components and elements of ProSkiND non-digital games framework based on the expert validation. A total of 12 experts were selected to validate the proposed main components and elements of the ProSkiND non-digital game using NGT online workshop. There were five main components with 41 elements were proposed: activity objective, teacher’s preparation, teacher’s role, children’s role, and activity evaluation. In this study, experts are asked to evaluate the ProSkiND non-digital games main components and elements based on the percentage value of agreement. The value of percentage of agreement that exceeds 70% (≥70%) is acceptable. The findings in this phase are used to develop main components and elements of the ProSkiND non-digital game framework based on problem solving skills for preschool early mathematics using the interpretive structural modelling (ISM) approach.